Lateglacial and Holocene chronology of climate‐driven postglacial landscape evolution in northeast Greenland - Garcia‐Oteyza, Julia (2024)
The Greenland Ice Sheet is highly sensitive to climate change, leading to significant retreat along its edges. This rapid ice loss contributes to rising sea levels and impacts the Earth’s climate stability. Understanding the extent of recent glacier retreat is crucial in order to determine if it is unprecedented or within ranges of natural variability. Palaeoenvironmental studies aim to identify past glacial phases and landscape changes using advanced dating methods such as cosmic ray exposure (CRE) dating. In NE Greenland, CRE dating has helped establish the timing of glacial oscillations, yet a comprehensive understanding of glacial fluctuations during specific periods still needs to be developed. This study aims to chronologically constrain the postglacial landscape evolution of two NE Greenland valleys from the Young Sund–Tyrolerfjord area (74°N, 20–25°E) from the onset of deglaciation and throughout the Holocene to better understand glacial and postglacial changes. The chronological framework relies on 27 10Be cosmic-ray exposure ages that constrain our interpretation of the geomorphological features in both valleys. Inconsistencies were observed in the ages dataset, highlighting potential bias associated with nuclide inheritance and post-glacial dynamics. Despite limitations, the CRE results confirm the general pattern observed in NE Greenland: (i) major deglaciation and disconnection of glaciers from the main glacial systems during the Lateglacial and Early Holocene with a rapid but not homogeneous deglaciation within the range from ~14.3 to 11.9 ka; (ii) no evidence of glacial activity during theMiddleHolocene, probably associatedwith the withdrawn position of theicemasses’fronts; and (iii) glacier expansion during the Late Holocene, with a Little Ice Age advance as the last significant period of glacial regrowth.